Current clinical practice gaps in the treatment of intermediate‐ and high‐risk non‐muscle‐invasive bladder cancer (NMIBC) with emphasis on the use of bacillus Calmette‐Guérin (BCG): results of an international individual patient data survey (IPDS). (1st March 2013) - Witjes, J. Alfred; Palou, Joan; Soloway, Mark; Lamm, Donald; Kamat, Ashish M.; Brausi, Maurizio; Persad, Raj; Buckley, Roger; Colombel, Marc; Böhle, Andreas
<x xml:space="preserve">Abstract</x> Objectives To examine the management of intermediate‐ and high‐risk non‐muscle‐invasive bladder cancer (NMIBC), particularly with regard to the use of bacillus Calmette‐Guérin (BCG) therapy, in North America and Europe. To compare NMIBC management practices to European Association of Urology (EAU) and American Urological Association (AUA) guideline recommendations for the management of intermediate‐ and high‐risk NMIBC. Patients and Methods In all, 102 urologists from Europe and North America participated in this retrospective on‐line chart review, which was conducted between 1 April 2011 and 30 April 2012. Participants selected the charts of the first 10 intermediate‐ (defined as multiple or recurrent low‐grade tumours) or high‐risk (defined as any T1 and/or high‐grade/G3 tumours and/or carcinoma in situ) patients who underwent transurethral resection of bladder tumour in 2009. Physicians retrospectively reviewed the charts and completed an on‐line survey consisting of questions related to diagnosis, planned treatment, treatment status and follow‐up. In all, 971 patients (197 intermediate‐risk; 774 high‐risk) were included in the analysis; frequency counts and associated percentages were used to analyse treatment variables. Results In all, 47% of intermediate‐risk patients received EAU or AUA guideline‐recommended intravesical therapy: intravesical chemotherapy, BCG induction therapy or BCG induction plus maintenance. Of the high‐risk patients, 50% received maintenance BCG as recommended by the EAU and the AUA; although not recommended for high‐risk NMIBC, 12.5% received intravesical chemotherapy. Of patients prescribed maintenance BCG, 93% were scheduled for at least 1 year of therapy. Notably, only 15% discontinued BCG maintenance and, of these discontinuations, 65% were due to reasons unrelated to BCG‐associated adverse events. Conclusions There is significant non‐adherence to EAU and AUA guideline recommendations for BCG use in intermediate‐ and high‐risk NMIBC. However, most of those patients prescribed BCG maintenance therapy are scheduled for at least 1 year of therapy, as recommended by current guidelines for NMIBC management, and BCG maintenance discontinuation is low.